Element of Corporate Governance in Islamic Banks vs Conventional Banks: A Case Study - Wijethunga, I. I.; Ekanayake, E. M. N. N. (American Research Institute for Policy Development, 2015)
Corporate governance (CG) have gained a prominent place in the sustainability of any institution, be it a corporate or a bank. Individuals lack detailed knowledge on the applicability of CG and its aspects in Islamic Banks (IBs) in contrast to Conventional Banks (CBs). Thus, the objective of this study is to explore ‘how’ and ‘why’ IBs differ from CBs in terms of structure of CG and its elements mainly board responsibilities, legal and regulatory compliance, internal control environment and auditing from a fundamental perspective. The study adopts interpretative methodology and multiple case study strategy in selecting one bank to represent each banking systems. Further, primary and secondary data were collected through interviews, observations, reports and websites. Major findings of the study concluded that IBs and CBs enclose differences as well as similarities pertaining to their CG and selected aspects. Major differences are driven connecting to the framework of IBs as they need to follow interest free paradigm, Profit and Loss Sharing paradigm and Shariah principles in performing the banking functions. Hence, these major principles have influenced for emergence of different CG structure in IBs.
Keywords: Islamic bank; Conventional bank; corporate governance; Profit and Loss Sharing paradigm; Shariah principals